Two pathways of costimulation through CD28 - Miller, Jim (Immunol Res, 2009)
CD28 is recognized as the primary costimulatory molecule involved in the activation of naïve T cells. However, the biochemical signaling pathways that are activated by CD28 and how these pathways are integrated with TCR signaling are still not understood. We have recently shown that there are at least two independent activation pathways induced by CD28 costimulation. One is integrated with TCR signaling in the context of the immunological synapse and is mediated through transcriptional enhancement and the second is mediated through the induction of mRNA stability. Here, we review the immunological consequences and biochemical mechanisms associated with CD28 costimulation and discuss the major questions that need to be resolved to understand the molecular mechanisms that transduce CD28 costimulation.